2023
DOI: 10.3390/catal13030551
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Surfactant-Assisted Liquid-Phase Exfoliation of Bi2S3 for Electrocatalytic Applications

Abstract: During water electrolysis, adding an electrocatalyst for the hydrogen evolution reaction (HER) is necessary to reduce the activation barrier and thus enhance the reaction rate. Metal chalcogenide-based 2D nanomaterials have been studied as an alternative to noble metal electrocatalysts because of their interesting electrocatalytic properties and low costs of production. However, the difficulty in improving the catalytic efficiency and industrializing the synthetic methods have become a problem in the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…− group forms a H-bond with water and stabilizes the exfoliated layers [25]. Our previous work also proves the possibility of exfoliation of Bi 2 S 3 with SDS [26]. Moreover, surfactants with a similar structure to SDS but different functional groups have been reported in LPE, such as sodium dodecylbenzene sulfonate (SDBS).…”
Section: Characterizationsmentioning
confidence: 57%
See 1 more Smart Citation
“…− group forms a H-bond with water and stabilizes the exfoliated layers [25]. Our previous work also proves the possibility of exfoliation of Bi 2 S 3 with SDS [26]. Moreover, surfactants with a similar structure to SDS but different functional groups have been reported in LPE, such as sodium dodecylbenzene sulfonate (SDBS).…”
Section: Characterizationsmentioning
confidence: 57%
“…Specifically, the intensity ratio of Ag mode and B1g mode is calculated to determine whether the samples were exfoliated [19,40]. In bulk Bi2S3, the Ag/B1g ratio is 1.68 [26], while for all the 4 displays the Raman spectra of Bi 2 S 3 samples with all the surfactants. It is possible to identify two main active modes, namely the B 1g and A g Raman modes, in all the samples.…”
Section: Uv-vis Analysismentioning
confidence: 99%
“…Wang et al conducted a study where they explored the impact of the initial bulk Bi 2 S 3 concentration in surfactant-assisted LPE while keeping other factors constant. 195 They observed that exfoliation yield remained consistently around 12% within the range from 0.33 mg mL −1 to 1.33 mg mL −1 of initial Bi 2 S 3 concentration. In this range, the exfoliation yield increased linearly with rising concentrations.…”
Section: Effects Of Starting Concentrationmentioning
confidence: 95%
“…(a) Exfoliation yield (black line) and concentration of LPE Bi 2 S 3 in SC/H 2 O suspensions (red line) after 3 h of sonication at different initial bulk Bi 2 S 3 concentrations. Reprinted under the terms of the CC-BY 4.0 license from ref . Copyright 2023 MDPI.…”
Section: Liquid Phase Exfoliationmentioning
confidence: 99%
“…34 To catalyze the OER, sulfur in Bi 2 S 3 integrates the layered structure and active species in the matrix with their direct and indirect roles depending on the content of sulfur ions in the matrix. 35 In the OER, exposed S vacancies and atoms on the Bi 2 S 3 plane and edges accelerate the OER activity directly, while when metals Bi and Sm act as active sites for the reaction the sulfur atom provides sites for the adsorption and desorption of radicals and catalyzes the OER activity indirectly. 36 In addition, localized and migratory 3d sulfide electrons in the Bi 2 S 3 hybrid with 3s and 3p sulfide electrons sustain the neighbor's cations in different configurations (trigonal, tetrahedral, octahedral, etc. )…”
Section: Introductionmentioning
confidence: 99%